Digital Business Leadership Digital Transformation, Business Model Innovation, Agile Organization, Change Management - Kreutzer, Ralf T. (Management for Professionals,, 2018)
This book provides specialists and executives with a clear, yet practical set of recommendations to meet the challenges of digital transformation and ensure long-term success as a leader in a primarily digital business world. The authors describe the fundamental principles of digitization and its economic opportunities and risks, integrating them into a framework of classic and new management methods. The book also explores how increasing digitization - not only of communication, but of complete value chains - has led to a need to establish a digital business leadership. Digitization is changing people and markets: it causes the upheaval of entire industries, creates new digital-centric companies, and forces established companies to cope with the transformation activities associated with these digitization processes. New approaches and methods have to be learned, tried and tested patterns of thinking have to be explored, and last but not least, innovation activities have to be understood as continuous necessities. At the same time, digital business offers considerable opportunities for renewing competitive advantages, improving existing process structures and realigning products, services and business models. .